Advances in the understanding of headache in idiopathic intracranial hypertension - Mollan, Susan P. (Curr Opin Neurol, 2019)
PURPOSE OF REVIEW: To review the most relevant developments in the understanding of headache in idiopathic intracranial hypertension (IIH). RECENT FINDINGS: The phenotype of the typical IIH headache is diverging from the historical thinking of a raised intracranial pressure headache, with the majority being classified as having migraine. A larger proportion of those with IIH have a past medical history of migraine, compared with the general population, highlighting the importance of re-examining those who have a change or escalation in their headache. The mechanisms underlying headache in IIH are not understood. Additionally, factors which confer a poor headache prognosis are not established. It is clear, however, that headache has a detrimental effect on all aspects of the patient's quality of life and is currently ranked highly as a research priority by IIH patients to better understand the pathophysiology of headache in IIH and identification of potential headache specific therapeutic agents. SUMMARY: Headache remains the predominate morbidity in the majority of those with IIH. Headache management is an unmet need in IIH and future studies are required to investigate the probable complex mechanisms, as well as effective management.